OPTIMIZATION OF SHOPEE MARKETPLACE IN INCREASING SALES VOLUME AT CV RABBANI ASSYSA JATINANGOR BRANCH - Rishyadi, Girda; Cecep Safa'atul Barkah; Tetty Herawaty; Lina Aulina (MANABIS: Jurnal Manajemen dan Bisnis, 2023)
The development of Muslim fashion in Indonesia is currently experiencing significant changes. Rabbani is a fashion outlet that is known by its consumers as a provider of Muslim clothing. Rabbani is a garment company engaged in the Muslim fashion sector. This study aims to provide an overview regarding how to optimize the marketplace shopee in increasing sales volume at CV Rabbani Assysa, Jatinangor Branch. The data analysis technique used is SWOT analysis. This study uses a research method with a qualitative approach. With the researcher as the main instrument. In this study, data sources were taken from primary data and secondary data. Primary data sources were collected directly through in-depth interviews with the head of the CV Rabbani Assysa store, Jatinangor branch. In addition, secondary data will be collected through a literature review based on findings from previous studies such as journals, articles, and books. Data collection techniques used are interviews and literature studies. References consist of journals, articles, and books that are relevant to this research. The data analysis technique used is SWOT analysis. SWOT analysis is used to analyze alternative marketing strategy factors that can be implemented by companies. The results of this study indicate that from the SWOT analysis that has been carried out, there is a strategy that can be proposed, namely increasing product marketing through online promotions, especially the marketplace shopee. By maximizing the use of marketplace shopee, sales will increase. In addition, by optimizing the marketplace, Shopee can also expand its market share. .